The postpartum period and mental health: women’s perceptions of their experiences and emotional challenges in the postpartum period - Candido Alsina , Camila; Bustamante Galarza , Karina (International Journal of Neurology, 2025)
Bacground: The puerperium is a stage of great physical and emotional transformations. Understanding women’s emotional experiences during this period is essential to improve family and professional accompaniment. Material and methods: A mixed, descriptive and cross-sectional study was carried out through a structured questionnaire distributed using Google Forms. 54 women over 18 years of age who went through the puerperium participated. The instrument included closed questions with a Likert scale of 1 to 5 and open-ended questions. The quantitative data were statistically analyzed, and the qualitative data were analyzed through thematic analysis. Results: Moderate levels of emotional support from the couple and family were identified. The emotional care provided by health professionals was perceived as limited. Frequent emotional symptoms such as anxiety, sadness, and feelings of guilt were also observed. Access to informational and psychological resources was insufficient. Conclusion: Participants evidenced significant emotional challenges during the postpartum period, especially in relation to access to professional and emotional support. The need for more humanized interventions focused on maternal mental health at this stage is highlighted.